Transportation of juvenile striped snakehead (Bloch 1793) with different densities in 3 ppt salinity media - Jannesa Nasmi; Kukuh Nirmala; Ridwan Affandi (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2017)
The present study aimed to ensure the effect 3 ppt of salt addition into the transportation media water to the water quality, suvival rate, daily growth rate, and stress level after transportation. This study was consisted of two phase, the first phase was fish transportation for 24 hours and the second phase was 21 days rearing after-transportation. Snake-head larvae’s transported with five treatments i.e a transportation media with no salt addition and stocked with 30 larvae L-1 as the control, and four transportation media with 3 ppt salt addition at different densities (30, 45, 60, and 75 larvae L-1). During the transportation, the water quality and survival rate were determined. The first phase experiment showed that salt addition in transportation media maintained the water quality and higher survival rate than control. After 24 hours, 30 larvae of each treatment were stocked into tank with 0 ppt salinity media. The results showed no significant differences in the survival rate and growth rate at the different densities without salt addition. The pH and blood glucose levels were slowly back to normal in day 21. Abstrak Tujuan penelitian ini adalah untuk menganalisis pengaruh pemberian garam 3 ppt dalam media pengangkutan terhadap perubahan kualitas air dan laju sintasan selama pengangkutan, laju pertumbuhan harian, glukosa darah, dan pH darah pascapengangkutan. Penelitian ini terdiri atas dua tahap kegiatan, yaitu tahap satu adalah pengangkutan selama 24 jam dan tahap dua adalah pemeliharaan pascapengangkutan selama 21 hari. Pada tahap satu kantong plastik diisi air 1 L dan dilakukan pengepakan sesuai dengan perlakuan, yaitu perlakuan kontrol tanpa garam (kepadatan 30 ekor L-1) dan perla-kuan penambahan garam 3 ppt (kepadatan 30, 45, 60, dan 75 ekor L